2003
DOI: 10.1093/brain/awg186
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the dissociation between singing and speaking in expressive aphasia

Abstract: We investigated the production of sung and spoken utterances in a non-fluent patient, C.C., who had a severe expressive aphasia following a right-hemisphere stroke, but whose language comprehension and memory were relatively preserved. In experiment 1, C.C. repeated familiar song excerpts under four different conditions: spoken lyrics, sung lyrics on original melody, lyrics sung on new but familiar melody and melody sung to a neutral syllable "la". In experiment 2, C.C. repeated novel song excerpts under three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
3
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 37 publications
6
70
3
3
Order By: Relevance
“…This interpretation is consistent with observations of isolable processing systems for speech and music (Hébert et al, 2003;Marin, 1982;Peretz & Coltheart, 2003;Peretz & Morais, 1993). KL's production errors are also consistent with this interpretation.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This interpretation is consistent with observations of isolable processing systems for speech and music (Hébert et al, 2003;Marin, 1982;Peretz & Coltheart, 2003;Peretz & Morais, 1993). KL's production errors are also consistent with this interpretation.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, KL's representation of verbally repeated phrases appeared more difficult to access, requiring a greater degree of verbal cueing and resulting in more frequent incomplete utterances. Overall, our findings may account for the previously reported paradoxical effect in the literature of preserved singing of familiar songs in patients with expressive aphasia, but the lack of an effect for unrehearsed sung over spoken novel stimuli in such patients (Cohen & Ford, 1995;Hébert et al, 2003;Peretz et al, 2004;Smith, 1966;Yamadori et al, 1977). In other words, melodic rehearsal appeared to be the key component for effecting longer-term improvements in speech production.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…On the one hand, several studies have found evidence suggesting autonomy of pitch processing in the two domains. Individuals with a disorder in one domain may have the other domain largely intact (Hébert, Racette, Gagnon, & Peretz, 2003;Peretz, Champod, & Hyde, 2003;Peretz & Coltheart, 2003;Racette, Bard, & Peretz, 2006;Schlaug, Marchina, & Norton, 2008;Ullman et al, 1997;Wilson, Parsons, & Reutens, 2006). Recent brain studies have pinpointed areas that are involved in linguistic pitch but not in music processing (Fedorenko, Behr, & Kanwisher, 2011).…”
Section: Introductionmentioning
confidence: 99%